Symposium on the economic outlook for 1954 - Carter, C. F.; Robson, P.; Cuthbert, Norman; Black, W. (Statistical and Social Inquiry Society of Ireland, 1954)
We are proceeding in this symposium from the general to the particular; and my task is to discuss in the broadest terms the general economic outlook for the United Kingdom in 1954. This seems to me to involve two questions, one for the short term and the other for the long. The short-term question is this: to which side shall we lean in the delicate balance between inflation and deflation? The first of these would be disastrous to our external accounts; the second is politically unthinkable, and would inflict grave suffering on Ulster. But we must not forget also the long-run problem: what progress are we making in adding to our national wealth, so that we may enjoy a rising standard of living and retain the power to compete in foreign markets?
Read before the Society, 12 March 1954
Keywords: Economic outlook; Economic growth; Irish economy in 1954; Business cycles; 314.15